Cloning and characterization of a basic cysteine-like protease (cathepsin L1) expressed in the gut of larval Diaprepes abbreviatus L. (Coleoptera: Curculionidae). (January 2015) - Ben-Mahmoud, Sulley; Ramos, John E.; Shatters, Robert G.; Rougé, Pierre; Powell, Charles A.; Smagghe, Guy; Borovsky, Dov
Graphical abstract: Highlights: Cathepsin L1 characterization. Inhibition studies. 3D modeling. EST library of larval gut digestome. Abstract: Diaprepes abbreviatus is an important pest that causes extensive damage to citrus in the USA. Analysis of an expressed sequence tag (EST) library from the digestive tract of larvae and adult D. abbreviatus identified cathepsins as major putative digestive enzymes. One class, sharing amino acid sequence identity with cathepsin L's, was the most abundant in the EST dataset representing 14.4% and 3.6% of the total sequences in feeding larvae and adults, respectively. The predominant cathepsin (Da-CTSL1) among this class was further studied. Three dimensional modeling of the protein sequence showed that the mature Da-CTSL1 protein folds into an expected cathepsin L structure producing a substrate binding pocket with appropriate positioning of conserved amino acid residues. A full-length cDNA was obtained and the proCTSL1 encoding sequence was expressed in Rosetta™ Escherichia coli cells engineered to express tRNAs specific for eukaryotic codon usage. The Da-CTSL1 was expressed as a fusion protein with GST and His6 tags and purified in the presence of 1% Triton X-100 by Ni-NTA affinity and size exclusion chromatography. Recombinant mature Da-CTSL1 (23 KDa) exhibits optimal activity at pH 8, rather than at acidic pH that was shown of all previously characterized cathepsins L. Substrate specificity supports the hypothesis that Da-CTSL1 is a unique basic cathepsin L and protease inhibitor studies also suggest unique activity, unlike other characterized acidic cathepsin Ls. This paper describes for the first time a prokaryotic expression system for the production of a functional eukaryotic cathepsin L1 from larval gut of D. abbreviatus .